Laboratory research for the chemical EOR projects: Case study in Serbia - Popić Darko; Pantić Jasna; Martinović Bojan; Crnogorac Miroslav (Podzemni Radovi)
During analysis of work process after first chemical EOR project done in Serbia it was observed that our available resources were not used in an optimal way. Some of laboratory tests that were part of standard testing procedures for selection of chemicals gave us little or non-useful information but took a lot of time and resources. This drove us to analyze all our available resources and to develop a process algorithm that will give us best "value for money spent" in terms of time optimization, and developing testing methodology that will utilize equipment that is already available in our laboratory. In a way, entire process was adapted to local conditions - focusing on conditions in Serbian oilfields and chemical selection methods needed for those conditions. The process described here is applied after chemical EOR method selection and it covers all possible combinations: Surfactant, Polymer, SP or ASP EOR. In case that one component is excluded, workflow can be modified with ease.